2020
DOI: 10.1021/acsomega.0c02878
|View full text |Cite
|
Sign up to set email alerts
|

Zizyphus mauritiana Fruit Extract-Mediated Synthesized Silver/Silver Chloride Nanoparticles Retain Antimicrobial Activity and Induce Apoptosis in MCF-7 Cells through the Fas Pathway

Abstract: Recently, green synthesis of silver/silver chloride nanoparticles (Ag/AgCl-NPs) has gained a lot of interest because of the usage of natural resources, rapidness, eco-friendliness, and benignancy. Several researchers reported that silver-based biogenic NPs have both antimicrobial and anticancer properties. In the present study, Ag/AgCl-NPs were synthesized from Zizyphus mauritiana fruit extract, and their antibacterial, antifungal, and antiproliferative mechanisms against human MCF-7 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 58 publications
0
17
1
Order By: Relevance
“…Many scientists reported that AgNPs induce apoptosis in a different cancer cell lines [45][46][47][48][49]. Several studies stated that cellular uptake of AgNPs leads to the generation of ROS in cancer cells, which provokes oxidative stress causing apoptosis [22] but we did not find ROS generation in treated HCT-116 and MCF-7 cells. Our study revealed that the synthesised Ag/AgCl-NPs could promote cell death without ROS generation.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Many scientists reported that AgNPs induce apoptosis in a different cancer cell lines [45][46][47][48][49]. Several studies stated that cellular uptake of AgNPs leads to the generation of ROS in cancer cells, which provokes oxidative stress causing apoptosis [22] but we did not find ROS generation in treated HCT-116 and MCF-7 cells. Our study revealed that the synthesised Ag/AgCl-NPs could promote cell death without ROS generation.…”
Section: Discussioncontrasting
confidence: 77%
“…The formation of nanoparticles was confirmed by UV–visible spectra analysis; morphological characterisation was carried out by TEM analysis; elemental characterisation was completed by EDX analysis; structural characterisation was carried out by XRD analysis and functional characterisation was carried out by FTIR analysis according to Kabir et al. [22] and the method is provided in supporting information S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These bands stained with dye gave straightforward evidence of the assembly of a stable 3-WJ structure. Different from silver chloride nanoparticles, 28 the size and the shape of DNA− AgNC particles are restricted by the DNA template. 29 As shown in Figure 2B, the uniform particles of AgNCs−ABL were around 3 nm, which was consistent with a previous report.…”
Section: Resultsmentioning
confidence: 99%
“…BIM is an apoptosis-inducing member of the Bcl-2 protein family and one of the potential mediators of p53-induced apoptosis [24,25]. Fas is another potential mediator of p53-induced apoptosis which belong to the classic - [26]. IGFBP5 has been demonstrated as a tumor suppressor which induced apoptosis and cell cycle arrest in breast cancer cells [27,28].…”
Section: Discussionmentioning
confidence: 99%